ANALISIS KINERJA KARYAWAN DIVISI PENGOLAHAN SAMPAH DAN LIMBAH B3 PADA CV TJEK ENTIS DI KOTA SURABAYA - Wiwik Handayani; Syahda Elma Rabihah (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
Human resources play an important role in achieving organizational goals, the ability of human resources must be thoroughly tested so that they are able to do all the work assigned to them. From the initial survey it is known that the high level of absenteeism of employees can affect organizational performance. The purpose of this study was to find out how the performance of employees of the B3 Waste and Waste Management Division at CV. Tjek Entis. The method used in this study is a survey method by distributing questionnaires to respondents. The sample used in this study were 50 employees. The results of this study show that quality, quantity, timeliness and cooperation are good. Whereas in the presence dimension there is an indicator with a low value, for that it is expected that the leader can provide motivation to employees with reward or punishment in order to increase employee attendance at work.